PENGARUH PENGGUNAAN PGPR (PLANT GROWTH PROMOTING RHIZOBACTERIA) TERHADAP INTENSITAS TMV (TOBACCO MOSAIC VIRUS), PERTUMBUHAN, DAN PRODUKSI PADA TANAMAN CABAI RAWIT (Capsicum frutescens L.) - Kamila Qurota A’yun; Tutung Hadiastono; Mintarto Martosudiro (Universitas Brawijaya, 2013)
One of the main disease of chili cultivation is mosaic disease that is caused byTMV (Tobacco Mosaic Virus). One effort to control the disease could be done byapplying Plant Growth Promoting Rhizobacteria (PGPR). PGPR is a usefulbacteria that lives and grows well in soil that contain much of organic matter. Thisresearch aimed to determine the effect of application and the role of PGPRPseudomonas fluorescens, Azotobacter sp., dan Bacillus subtilis on TMV attackintensity, the height and production of chili plant. This research was conducted inscreen house and plant disease laboratory, Brawijaya University Malang. Theexperiment started in April until August 2012. This research was using completerandomized design. The treatments used one species of PGPR bacteria and thecombination of two species of PGPR bacteria. The PGPR were PGPR P.fluorescens, PGPR Azotobacter sp., or PGPR B. subtilis. Whereas the PGPRcombination were PGPR P. fluorescens and PGPR Azotobacter sp., PGPR P.fluorescens and PGPR B. subtilis, or PGPR Azotobacter sp. and PGPR B. subtilis.Control were executed without applying PGPR. Results showed that thecombination of P. fluorescens and Azotobacter sp. PGPR affected on reducing theincubation periode, the attack intensity of TMV, and increasing the plant height.The incubation periode for chili plants with PGPR P. fluorescens and Azotobactersp. was 16,67 days. The PGPR P. fluorescens and Azotobacter sp. reduced TMVattack intensity on chili plants until 89,92%. The plant height of chili plants withPGPR P. fluorescens and Azotobacter sp. could reach 69,25 cm. PGPR P.fluorescens dan B. subtilis treatment could increase the average fruit weight ofchili until 2,17 grams per plant.Keywords: PGPR, Pseudomonas fluorescens, Azotobacter sp., Bacillus subtilis,TMV, chili